A performance indicator for structures under natural fire. (1st October 2015) - Gernay, T.; Franssen, J.-M.
Highlights: Structural failure may occur during or after the cooling phase of a fire. All typologies of structural components are concerned by delayed failures. An indicator is proposed to quantify a component vulnerability to delayed failure. It is used to compare the performance of different components in natural fire. Abstract: Fires in buildings are characterized by a heating phase followed by a cooling phase, yet the effects of the latter on structures are not well covered in the current approaches to structural fire engineering. Indeed the actual requirement of non-occurrence of structural failure at peak temperature does not guarantee against a delayed failure during or after the cooling phase of a fire, which puts at risk the fire brigades and people proceeding to a building inspection after a fire. Therefore there is an urgent need to better comprehend and characterize the materials and structures behavior under decreasing temperatures. Sensitivity to delayed failure of a structural component depends on its typology and constituting materials. In particular, two structural components with the same Fire Resistance rating ( R ) under standardized fire may exhibit very distinct behavior under natural fire, one of them being more prone to delayed failure than the other. With the aim of quantifying this effect, a new indicator is proposed that characterizes the performance of structures under natural fire conditions. The paper presents the methodology to derive this new indicator as well as results for different typologies of structural components. Parametric analyses highlight the prime influence of constitutive material and thermal inertia of the element on the post-peak behavior. Used in conjunction with the Fire Resistance rating, it is shown how the new indicator carries additional and significant information for classifying structural systems in terms of their fire performance and propensity to delayed failure.